A Simulation of University Marketing Strategies Through Print and Digital Advertising Media: Simulasi Pemasaran Universitas dalam Media Iklan Cetak ataupun Online - Ega Adrianto; Ignatius Luddy Indra Purnama; Karina Amanda Larasati; Edo Ariful Hudha (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to analyze the effectiveness of higher education promotional media in attracting prospective students’ attention, particularly among recently graduated high school students, by comparing traditional and digital advertising media. The analysis was conducted by measuring the duration of students’ attention toward each type of promotional media displayed during the process of searching for university information. The results indicate that traditional promotional media, such as education expos and billboards, still play an effective role in increasing institutional awareness and attracting prospective students’ attention. On the other hand, digital media such as social media and websites provide faster, broader, and more interactive access to information for prospective students, parents, and teachers. These findings suggest that higher education institutions need to optimally integrate traditional and digital promotional strategies to enhance marketing communication effectiveness and strengthen institutional competitiveness in the digital era.